6‐GHz‐to‐18‐GHz AlGaN/GaN Cascaded Nonuniform Distributed Power Amplifier MMIC Using Load Modulation of Increased Series Gate Capacitance. Issue 5 (11th October 2017) - Shin, Dong‐Hwan; Yom, In‐Bok; Kim, Dong‐Wook
Abstract : A 6‐GHz‐to‐18‐GHz monolithic nonuniform distributed power amplifier has been designed using the load modulation of increased series gate capacitance. This amplifier was implemented using a 0.25‐μm AlGaN/GaN HEMT process on a SiC substrate. With the proposed load modulation, we enhanced the amplifier's simulated performance by 4.8 dB in output power, and by 13.1% in power‐added efficiency (PAE) at the upper limit of the bandwidth, compared with an amplifier with uniform gate coupling capacitors. Under the pulse‐mode condition of a 100‐μs pulse period and a 10% duty cycle, the fabricated power amplifier showed a saturated output power of 39.5 dBm (9 W) to 40.4 dBm (11 W) with an associated PAE of 17% to 22%, and input/output return losses of more than 10 dB within 6 GHz to 18 GHz.